Circular RNA Circ_0001322 inhibits gastric cancer progression by modulating the miR-1264/QKI axis and suppressing the Hedgehog pathway: Circ_0001322 inhibits GC progression - Wu, Wenyi; Cai, Yiqi; Jin, Jinji; Chen, Zhejing; Teng, Mujian (Cellular and Molecular Biology, 2024)
Circular RNA hsa_circ_0001322 (circ1322) was demonstrated to be significantly reduced in expression in gastric cancer patients in our previous study, and changes in its expression were significantly correlated with lymph node metastasis. However, the underlying workings of circ1322 in gastric cancer are still not fully understood. Therefore, to confirm the effect of circ1322 on gastric cancer, we examined the expression of circ1322 in gastric cancer cells and tissues. The results showed that circ1322 was lowly expressed in GC tissues and cells. Subsequently, we further performed cellular assays and animal experiments, which showed that Circ1322 upregulation inhibited GC cell proliferation, migration and invasion. while promoting GC cell apoptosis, and inhibited tumor growth in mice. The direct targeting of circ1322 to miR-1264 was confirmed by bioinformatics prediction and validation of luciferase reporter gene assay. Circ1322 can act as a miR-1264 sponge to alleviate the inhibitory effect of miR-1264 on its target gene, QKI. miR-1264 regulates the expression of QKI and the activity of the hedgehog pathway. That is, circ1322 may act as a competing endogenous RNA (ceRNA) to inhibit the hedgehog pathway by targeting the miR-1264/QKI axis, which in turn promotes GC progression.